Characterization of the Anti-Inflammatory Capacity of IL-10-Producing Neutrophils in Response to Streptococcus pneumoniae Infection - González, Liliana A.; Melo-González, Felipe; Sebastián, Valentina P.; Vallejos, Omar P.; Noguera, Loreani P.; Suazo, Isidora D.; Schultz, Bárbara M.; Manosalva, Andrés H.; Peñaloza, Hernán F.; Soto, Jorge A.; Parker, Dane; Riedel, Claudia A.; et al. (Frontiers in Immunology, 2021)
Neutrophils are immune cells classically defined as pro-inflammatory effector cells. However, current accumulated evidence indicates that neutrophils have more versatile immune-modulatory properties. During acute lung infection with Streptococcus pneumoniae in mice, interleukin-10 (IL-10) production is required to temper an excessive lung injury and to improve survival, yet the cellular source of IL-10 and the immunomodulatory role of neutrophils during S. pneumoniae infection remain unknown. Here we show that neutrophils are the main myeloid cells that produce IL-10 in the lungs during the first 48 h of infection. Importantly, in vitro assays in bone-marrow-derived neutrophils confirmed that IL-10 can be induced by the direct recognition of pneumococcal antigens. In vivo, we identified the recruitment of two neutrophil subpopulations in the lungs following infection, which exhibited clear morphological differences and a distinctive profile of IL-10 production at 48 h post-infection in vivo. Furthermore, adoptive transfer of neutrophils from WT mice into IL-10 knockout mice (Il10-/-) fully restored IL-10 production in the lungs and reduced lung histopathology. These results suggest that IL-10 production by neutrophils induced by S. pneumoniae limits lung injury and is important to mediate an efficient immune response required for host survival.